Hallazgos clínico-radiológicos de la articulación temporomandibular en pacientes con artritis reumatoide - Chávez Andrade, Gisselle M. [UNESP] (2009)
Aim of present paper is to describe and to assess the Clinicoradiological findings of the temporomandibular joint (TMJ) in a group of patients diagnosed with rheumatoid arthritis (RA). Sample included 61 patients with a mean age of 54 years and 5 months. All of them were interrogated and clinically examined and then underwent to a radiographic examination of both TMJs, using the transcranial projection technique, with the closed mouth and in maximal opening. Study includes the TMJ syndrome founded such as pain, tumefaction, luxation, clicking, and a limited oral opening. The study of radiographic features showed the presence of changes in condyle surface and temporal fossa, in condylar motility, and articulation space. We conclude that in patients presenting with rheumatoid arthritis is frequent the presence of clinicoradiological findings in the TMJ, and that patient's age and gender and the activity level and the RA course time, are factors influencing in TMJs general status.